Springback compensation of automotive panel based on three-dimensional scanning and reverse engineering. Issue 5 (July 2016) - Wang, Hui; Zhou, Jie; Zhao, Tiansheng; Tao, Yaping
Abstract A new method to compensate for the springback of a formed part was introduced in this study. The development of stamping tools for the rear reinforcement plate of a door panel was used for the experiment. A three-dimensional (3D) scanner was utilized to scan the formed part. Compared with the design model, the deviation and springback angle of the formed part were obtained. Furthermore, the inspection results measured by a traditional special fixture were compared with the results of the 3D scanner. Finally, the 3D scanning data were used to compensate tool surfaces, and the tools were remanufactured on the basis of the compensated tool surfaces. The final stamping parts were measured by a special fixture after die tryout. The inspection results demonstrated that 15 of 18 measuring points can satisfy the geometrical tolerances, thus indicating that the qualified rate of this product can reach 83.33 % the first time the springback is compensated by using 3D scanning method. The results prove that 3D scanning data is more accurate and complete than the traditional method, and the springback compensation by this method can effectively reduce die tryout time.